Characterization of fungi isolated from the equipment used in the International Space Station or Space Shuttle. (May 2016) - Satoh, Kazuo; Yamazaki, Takashi; Nakayama, Takako; Umeda, Yoshiko; Alshahni, Mohamed Mahdi; Makimura, Miho; Makimura, Koichi
ABSTRACT: As a part of a series of studies regarding the microbial biota in manned space environments, fungi were isolated from six pieces of equipment recovered from the Japanese Experimental Module "KIBO" of the International Space Station and from a space shuttle. Thirty‐seven strains of fungi were isolated, identified and investigated with regard to morphological phenotypes and antifungal susceptibilities. The variety of fungi isolated in this study was similar to that of several previous reports. The dominant species belonged to the genera Penicillium, Aspergillus and Cladosporium, which are potential causative agents of allergy and opportunistic infections. The morphological phenotypes and antifungal susceptibilities of the strains isolated from space environments were not significantly different from those of reference strains on Earth.